EL DEPORTE COMO HERRAMIENTA ESTRATÉGICA EN LA CONSTRUCCIÓN DE LA MARCA CANAL + ESPAÑA - Lic. Santiago MAYORGA ESCALADA,Cat. Luis Miguel PEDRERO ESTEBAN, (Fonseca, Journal of Communication, 2023)
The identity of an institution or company is the based to its activity and to the perception by the public, a purpose for which it is essential the building a brand image. This communication describes and analyzes how the positioning and branding of Canal + Spain since its launch in the television market at 1990 was conceived, and how the sports were articulated early on as one of the differential and decisive elements in the consolidation of this brand.